Pathology of Angiostrongylus cantonensis infection in two model avian hosts. Issue 2 (28th February 2021) - Fecková, Barbora; Djoehana, Priyanka; Putnová, Barbora; Valašťanová, Michaela; Petríková, Michaela; Knotek, Zdeněk; Modrý, David
Abstract: Angiostrongylus cantonensis causes severe neurological disorders in a wide range of warm-blooded animals, including several avian species. A laboratory isolate of A. cantonensis originating from French Polynesia, genotyped as clade 2, was used to assess the effect of experimental infection in chicken and Japanese quail. Low dose groups of birds were infected orally by 100 L3 larvae, high dose groups by 1500 L3 larvae and the birds in the third group were fed three infected snails, mimicking a natural infection. Clinical signs during the first week after infection, haematology, biochemistry, gross lesions and histology findings were used to assess the pathology of the infection. Some of the infected birds showed peripheral eosinophilia, while mild neurological signs were seen in others. No larvae were observed in serial sections of the central nervous system of infected birds 1 week after infection and no major gross lesions were observed during necropsy; histopathology did not reveal lesions directly attributable to A. cantonensis infection. Our results suggest that galliform birds are not highly susceptible to A. cantonensis infection and open a question of the importance of Galliformes in endemic areas as natural pest control, lowering the number of hosts carrying the infective larvae.